Electronically Conductive Hydrogels by in Situ Polymerization of a Water‐Soluble EDOT‐Derived Monomer. Issue 10 (22nd May 2022) - Nguyen, Dan My; Wu, Yuhang; Nolin, Abigail; Lo, Chun-Yuan; Guo, Tianzheng; Dhong, Charles; Martin, David C.; Kayser, Laure V.
Abstract : Electronically conductive hydrogels have gained popularity in bioelectronic interfaces because their mechanical properties are similar to biological tissues, potentially preventing scaring in implanted electronics. Hydrogels have low elastic moduli, due to their high water content, which facilitates their integration with biological tissues. To achieve electronically conductive hydrogels, however, requires the integration of conducting polymers or nanoparticles. These "hard" components increase the elastic modulus of the hydrogel, removing their desirable compatibility with biological tissues, or lead to the heterogeneous distribution of the conductive material in the hydrogel scaffold. A general strategy to transform hydrogels into electronically conductive hydrogels without affecting the mechanical properties of the parent hydrogel is still lacking. Herein, a two‐step method is reported for imparting conductivity to a range of different hydrogels by in‐situ polymerization of a water‐soluble and neutral conducting polymer precursor: 3, 4–ethylenedioxythiophene diethylene glycol (EDOT‐DEG). The resulting conductive hydrogels are homogenous, have conductivities around 0.3 S m −1, low impedance, and maintain an elastic modulus of 5–15 kPa, which is similar to the preformed hydrogel. The simple preparation and desirable properties of the conductive hydrogels are likely to lead to new materials and applications in tissue engineering, neural interfaces, biosensors, and electrostimulation. Abstract : The incorporation of a conducting polymer in hydrogels is a common strategy to achieve electrically conductive hydrogels. However, the addition of a "hard" conducting polymer often increases the elastic modulus of the parent hydrogel. Instead, this study uses a conducting polymer with ethylene glycol side chains to maintain a low modulus while imparting good electronic and ionic conductivity.